Ascorbic Acid Significantly Decreases Creatine Kinase Plasma Levels in an Animal Model of Statin/Fibrate-Induced Myopathy - Mohsen Zabihi; Fatemeh Askarian; Seyedhossein Hekmatimoghaddam; Mohammadreza Rashidi Nooshabadi; Mohammad Sajjad Zabihi; Seyed Ruhollah Mousavinasab (Advances in Pharmacological and Pharmaceutical Sciences)
Background. Myopathy is one of the side effects of lipid-lowering drugs, especially statins and particularly when combined with a fibrate. To diagnose myopathy and determine its severity, the plasma levels of three enzymes, creatine kinase (CK), aldolase, and lactate dehydrogenase (LDH), are routinely measured. Physical exercise can aggravate the statin-associated muscular disease. The question is whether antioxidants like ascorbic acid (Vit. C) can prevent such myopathy. Methods. In this experiment, a combination of atorvastatin (ATV, 80 mg/kg/day) and gemfibrozil (GMF, 1000 mg/kg/day) orally for 10 days as well as exercise as forced swimming on days 8, 9, and 10 were used to induce myopathy. Ascorbic acid (50 mg/kg/day, orally) was added to ATV/GMF plus exercise regimen throughout the 10 days in the treatment group. Mean blood levels of CK, aldolase, and LDH were measured in addition to swimming tolerance times. Results. There was a significantly higher swimming tolerance time P<0.05 and lower CK levels P<0.01 in rats receiving ATV/GMF/Vit. C plus exercise compared with rats not taking Vit. C. LDH and aldolase did not decrease significantly. Conclusion. The results of this study showed that Vit. C can be effective in preventing myopathy caused by fat-lowering drugs.